2015
DOI: 10.1002/adma.201404891
|View full text |Cite
|
Sign up to set email alerts
|

Highly Circularly Polarized Electroluminescence from a Chiral Europium Complex

Abstract: The first circularly polarized OLED (CP-OLED) based on a chiral lanthanide complex is developed. With a simple architecture, this proof-of-concept device attains the highest polarization reported so far and additionally presents the first example of a Ln-based OLED that can be turned into a CP-OLED, fully retaining the special features of Ln-based OLEDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
320
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 415 publications
(328 citation statements)
references
References 28 publications
6
320
1
1
Order By: Relevance
“…Using a theoretical analysis incorporating the Stokes parameter, the twisting angle and birefringence of the aligned conjugated polymer, and the degree of linear polarization in the emitted light are found to make a roughly equal contribution to the degree of CPEL as to the degree of CPPL. [8][9][10] In the latter case, although it directly emitted high degree of CP light, selection of material is limited and it is necessary to select a host material having suitable characteristics to realize an electroluminescent device. This result is applied to an organic light-emitting display to improve the luminous efficiency by 60%.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Using a theoretical analysis incorporating the Stokes parameter, the twisting angle and birefringence of the aligned conjugated polymer, and the degree of linear polarization in the emitted light are found to make a roughly equal contribution to the degree of CPEL as to the degree of CPPL. [8][9][10] In the latter case, although it directly emitted high degree of CP light, selection of material is limited and it is necessary to select a host material having suitable characteristics to realize an electroluminescent device. This result is applied to an organic light-emitting display to improve the luminous efficiency by 60%.…”
mentioning
confidence: 99%
“…Moreover, it is also found that the location of the recombination zone within the emitting layer is a crucial parameter for determining the difference in the dissymmetry factor between CPEL and CPPL. [8,10] Therefore, it has been extensively studied about supramolecular helical structure emitting CP light (T1). Electroluminescence The direct emission of circularly polarized (CP) light from conjugated polymers upon photo-or electro-excitation is a key feature for displays, optical data storage, optical quantum information, and chirality sensing.…”
mentioning
confidence: 99%
“…The promising features of the CPL make us prospect immediate applications: in the first place, one can envisage a security ink which can emit red circularly polarized light under blue-light illumination, secondly, our recent experience with circularly polarized light emitting devices (CP-LED) 28 make us wonder if the ease of excitation of the ligand will have consequences in electroluminescence, as it does with photoexcitation. For these reasons, we attempted by all means to isolate the active species, which unfortunately resulted elusive.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…The fallouto ft hese predictionsw ill be to better rationalize the fundamental chiroptical spectra of lanthanides, especially in connection with their use as luminescent materials. [23,24] …”
Section: Introductionmentioning
confidence: 99%